PENGARUH PERMAINAN FLASHCARD DALAM MENGEMBANGKAN KEMAMPUAN BERBICARA PADA ANAK - Putri Wulandini; Adelia Putri; Sukarni (LPPM Universitas Abdurrab, 2025)
Introduction The characteristics of speaking skills in children are seen based on the age range of children 4-6 years old who are able and can do any of the characteristics above. Flashcard media is a small card containing an image, text or symbol that reminds or leads students to something related to the image. Flashcards can help introduce various materials easily. The purpose of this case study is to determine the effect of flashcard games before and after the action is given. The research method used is pre-experimental design in the form of one group test. The study was conducted in November-December 2023, with 39 children responding. The data collection techniques used are observation sheet and documentation. Data processing using Chi-Square test analysis. The results of this study show that there is an influence on the development of speech skills. Evidenced by the increase in the average posttest speaking ability (1.67) higher than the pretest of speaking ability (1.28). The results of the chi-square test obtained a p-value = 0.0017<0.05 so that there is an influence. The implication of this study is that for teachers in kindergarten are advised to use flashcard media in developing children's ability to speak. Playing flashcards can stimulate children to express perceptions, memories, thoughts, including in developing vocabularry